Determination of gross alpha and beta activity and uranium isotope content in commercially available, bottled, natural spring waters - Nuhanović, Mirza; Mulić, Mirela; Mujezinović, Aida; Grgić, Željka; Bajić, Irma (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2015)
Determination of content (active concentration) of radio-nuclides has recently become an indispensable part of the study dealing with the protection of the environment. Uranium concentration levels in aquatic environment are of great importance for environmental and safety assessment and for the protection of public health. Achieving this purpose, monitoring program for this radio-nuclide, radium and thorium, as well as gross alpha and beta activities, seems necessary and it is applied in many countries. This study determined the activity concentration of uranium isotopes in 10 samples of drinking water, natural spring and mineral water (bottled, commercially available water). Also, gross alpha and beta activity has been determined for all samples. Activity concentration of uranium isotopes was measured with alpha-spectrometry, while gross alpha-beta activity was measured by low level gas-flow proportional alpha-beta counter. Results of the research show that the concentration of isotopic uranium activities in the tested samples of drinking water varies from 10-8 to 10-2 Bq/L, while gross alpha-beta activity is between 10-3 and 10-1 Bq/g. The results show that the analyzed brands of spring, commercially available bottled waters meet the defined criteria of radiological safety.